Nursing Informatics and Leadership, an Essential Competency for a Global Priority: eHealth - Hussey, P.; Adams, Elisabeth; Shaffer, F. (2015)
Contemporary healthcare delivery is at an intersection. On one hand, policymakers and researchers strongly advocate self-care management programs, patient empowerment, and promotion of community-based services. Conversely, hospital centrism and hyper-specialization continue to prevail. Reporting in 2008, the World Health Organisation (WHO) argued the case that the medical model invariably fails to deliver affordable, accessible, and equitable health for citizens.1 This failure can be linked with strong commercial undertones and medical models that, from the patient’s view, often results in a fragmentation of care. Since this report was published by WHO in 2008, the need to address the fragmentation of care unfortunately persists. More recent resources by WHO include an eHealth Toolkit that provides strategic guidance to leaders in relation to an eHealth vision for all.